Effects of long-term anti-seizure medication monotherapy on all-cause death in patients with post-stroke epilepsy: a nationwide population-based study in Taiwan - Chia-Yu Hsu; Chun-Yu Cheng; Jiann-Der Lee; Meng Lee; Bruce Ovbiagele (BMC Neurology, 2021)
Abstract Objective We aim to compare the effect of long-term anti-seizure medication (ASM) monotherapy on the risk of death and new ischemic stroke in patients with post-stroke epilepsy (PSE). Patients and methods We identified all hospitalized patients (≥ 20 years) with a primary diagnosis of ischemic or hemorrhagic stroke from 2001 to 2012 using the National Health Insurance Research Database in Taiwan. The PSE cohort were defined as the stroke patients (1) who had no epilepsy and no ASMs use before the index stroke, and (2) who had epilepsy and ASMs use after 14 days from the stroke onset. The patients with PSE receiving ASM monotherapy were enrolled and were categorized into phenytoin, valproic acid, carbamazepine, and new ASM groups. We employed the Cox regression model to estimate the unadjusted and adjusted hazard ratios (HRs) with 95 % confidence intervals (CIs) of death and new ischemic stroke within 5 years across all groups, using the new ASM group as the reference. Results Of 6962 patients with PSE using ASM monotherapy, 3917 (56 %) were on phenytoin, 1623 (23 %) on valproic acid, 457 (7 %) on carbamazepine, and 965 (14 %) on new ASMs. After adjusting for confounders, compared with new ASM users, phenytoin users had a higher risk of death in 5 years (HR: 1.64; 95 % CI: 1.06–2.55). On the other hand, all ASM groups showed a similar risk of new ischemic stroke in 5 years. Conclusions Among patients with PSE on first-line monotherapy, compared to new ASMs, use of phenytoin was associated with a higher risk of death in 5 years.